2018
DOI: 10.1590/s1980-6574201800040015
|View full text |Cite
|
Sign up to set email alerts
|

The role of body fat in the relationship of cardiorespiratory fitness with cardiovascular risk factors in Brazilian children

Abstract: To analyze the association between the percentage of body fat and cardiorespiratory fitness (CRF) with cardiovascular risk factors in children, and; to examine whether percentage of body fat acts as a mediator on the association between CRF and cardiovascular risk factor. Methods: This cross-sectional study included 128 children aged 7-11 years (Mean 8.54, SD: 1.42). The following variables were evaluated: the percentage of body fat, CRF, diastolic and systolic blood pressure, glucose, triglycerides (TG) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Another study showed that CRF is the link of less BC associated with better cardiometabolic health (ANDERSEN et al, 2015). Besides, another aut hors showed that BC can be an intervenient negative factor for the CRF relation with less cardiometabolic risk (BRAND et al, 2018;GRALLA et al, 2019;PÉREZ-BEY et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another study showed that CRF is the link of less BC associated with better cardiometabolic health (ANDERSEN et al, 2015). Besides, another aut hors showed that BC can be an intervenient negative factor for the CRF relation with less cardiometabolic risk (BRAND et al, 2018;GRALLA et al, 2019;PÉREZ-BEY et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…However, in practice and applicable view for physical education teaching and management of physical exercise for children health promotion (KAHAN;LOUNSBERY, 2013), the upper cited studies thesis suggested when there is an improvement, as a fatness decrease in BC also there is an increase in CRF and vice versa HALLAL, 2014;FAIRCLOUGH, 2003;GORAN et al, 2000;GRALLA et al, 2019;MCMURRAY et al, 1998;MILANESE et al, 2020). Some of these results come from mediation analyses conception (BRAND et al, 2018;PÉREZ-BEY et al, 2019;WISNIESKI;DALIMONTE-MERCKLING;ROBBINS, 2019). It is probably that mediation analyses are possible and applicable because of the CRF positive relation with lean body mass HALLAL, 2014;FAIRCLOUGH, 2003;GORAN et al, 2000;GRALLA et al, 2019;MCMURRAY et al, 1998;MILANESE et al, 2020) and it is due to the maximal volume of oxygen (vo2máx) is relative and indissociable of the total body mass and BC measures when measured in field tests battery (BERGMANN et al, 2014;VALENTE-DOS-SANTOS et al, 2015;WERNECK et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study investigating this hypothesis in older adults. Other studies show that fatness is a mediator of muscular fitness and metabolic syndrome [44] in adolescents and, similarly, Brand et al [45] and Bailey et al [46] found that body fat mediated the relationship between cardiorespiratory fitness and cardiovascular risk factors. Also, it has been shown that patients with T2DM and with visceral fat accumulation have low muscle quality [47].…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, the effects of bF on CrF can be mediated by mean arterial pressure (MaP). a higher percentage of bF is associated with higher MaP [45]. however, some other factors, such as genetics and gender, may have an influence on the status of body composition and CrF [31,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%